PENGARUH MODEL PEMBELAJARAN SCRAMBLE TERHADAP HASIL BELAJAR PADA MATERI BUDAYA DAERAHKU SISWA KELAS V SDN 2 RIAU SILIP - Oktarina, Diyatri; Kurnia, Feni; Nabela, Silvio Juliana (LEARNING : Jurnal Inovasi Penelitian Pendidikan dan Pembelajaran, 2025)
The impetus for this research was the suboptimal academic achievement among fifth-grade students at SDN 2 Riau Silip, particularly in the "Budaya Daerahku"  unit. This situation was identified as a consequence of the dominance of conventional pedagogy and minimal active student participation. Baseline data confirmed this issue, with a mean score of 47.6 indicating that the majority of students had not yet met the Minimum Mastery Criteria (KKTP).Grounded in this context, the study was focused on investigating the effectiveness of the Scramble learning model on student learning outcomes for the related material. This research adopted a quantitative approach utilizing a quasi-experimental, non-equivalent control group design. The population involved in this study included the total fifth-grade student body at SDN 2 Riau Silip.The sampling technique employed was saturated sampling, wherein the entire population served as the research sample. These subjects were subsequently divided into two cohorts: an experimental group, which received the pedagogical intervention of the Scramble model, and a control group, which continued to receive instruction via conventional methods.The primary data collection instrument was an essay test, administered in two phases (as a pre-test and a post-test). Analysis of the collected data involved a series of prerequisite tests, including normality and homogeneity tests, before proceeding to hypothesis testing using a t-test.Research findings indicated a statistically significant disparity in student learning outcomes post-intervention. Specifically, the experimental group demonstrated an increase in average scores, moving from 44.80 (on the pre-test) to 60.4 (on the post-test).Verification through hypothesis testing reinforced this finding, wherein the calculated t-value  of 2.346 was proven to exceed the critical t-value  of 2.059. This statistical comparison provided the basis for rejecting the null hypothesis (Ho) and accepting the alternative hypothesis (Ha). In conclusion, the Scramble learning model was demonstrated to have a significant effect on the learning outcomes of fifth-grade students at SDN 2 Riau Silip for the "Budaya Daerahku" material. ABSTRAKPenelitian ini dilatarbelakangi oleh hasil belajar siswa kelas V di SDN 2 Riau Silip yang kurang memuaskan pada materi "Budaya Daerahku", yang disebabkan oleh pendekatan pengajaran tradisional dan kurangnya partisipasi siswa. Nilai rata-rata awal sebesar 47,6 menunjukkan bahwa banyak siswa belum memenuhi standar yang dipersyaratkan untuk menyelesaikan Tujuan Pembelajaran. Tujuan penelitian dilakukan untuk mengkaji bagaimana strategi pembelajaran Scramble memengaruhi hasil belajar siswa di bidang ini. Pendekatan kuantitatif digunakan, menggunakan desain kuasi eksperimental dengan kelompok kontrol non ekuivalen. Seluruh 50 siswa kelas V di SDN 2 Riau Silip merupakan populasi penelitian. Partisipan dalam penelitian ini terdiri dari siswa kelas V yang dibagi menjadi kelompok eksperimen, yang diajar menggunakan model Scramble, dan kelompok kontrol, yang diajar menggunakan metode standar. Strategi pengambilan sampel jenuh digunakan, yang berarti semua anggota populasi diikutsertakan dalam sampel. Ujian esai, yang diberikan sebagai pretestt dan posttest, digunakan untuk mengumpulkan data. Data dianalisis menggunakan uji normalitas dan homogenitas, serta uji hipotesis menggunakan Uji-T Sampel Independen. Hasilnya menunjukkan perubahan yang signifikan dalam prestasi akademik siswa setelah intervensi. Skor rata-rata kelompok eksperimen meningkat dari 44,80 pada pretest menjadi 60,4 pada posttest. Uji hipotesis menunjukkan bahwa nilai t hitung (2,346) melebihi nilai t tabel (2,059). Akibatnya, hipotesis nol (Ho) ditolak, dan hipotesis alternatif (Ha) dikonfirmasi. Kesimpulannya adalah bahwa strategi pembelajaran Scramble memiliki dampak yang signifikan terhadap prestasi akademik siswa kelas V di SDN 2 Riau Silip dalam mempelajari budaya daerah mereka.